ChemInform Abstract: Asymmetric Synthesis Approach of Enantiomerically Pure Spiro‐Indenoquinoxaline Pyrrolidines and Spiro‐Indenoquinoxaline Pyrrolizidines. Issue 15 (24th March 2016) - Shahrestani, Naeimeh; Salahi, Farbod; Tavakoli, Niloofar; Jadidi, Khosrow; Hamzehloueian, Mahshid; Notash, Behrouz
Abstract: An one‐pot, four‐component procedure for the synthesis of title compounds such as (V) and (IX) with high regio‐ and diastereoselectivity, through 1, 3‐dipolar cycloaddition of in situ generated azomethine ylides and a cinnamoyl/crotonoyl oxazolidinone (III) is described.